Oral cavity swabbing for diagnosis of group a Streptococcus: a prospective study - Limor Adler; Miriam Parizade; Gideon Koren; Ilan Yehoshua (BMC Family Practice, 2020)
Abstract Background Throat pain is a common complaint in the ambulatory setting. Diagnosis of group A Streptococcus is made with a culture, molecular test or a rapid antigen detection test from the tonsils or the posterior pharyngeal wall, while other areas of the oral cavity are considered unacceptable. The purpose of the study is to compare cultures from the tonsils or posterior pharyngeal wall (throat) with cultures from the oral cavity (mouth). Methods A prospective study conducted in ambulatory care. Eleven family physicians collected 2 swabs (throat and mouth) from 200 consecutive patients who complaint about throat pain. Inclusion criteria were throat pain and Centor Criteria > 2. Exclusion criteria were tonsillectomy and age (< 3 or > 65 years old). Participants were later divided into two groups – pediatrics (3–18 years old) and adults (19–65 year old). Sensitivity and specificity of mouth culture were calculated, with throat culture considered the reference gold standard. Results Between November 2017 and March 2019, 200 swabs were collected (101 adults and 99 children). In the adult group sensitivity of mouth culture was 72.1% (95% Confidence Interval [CI] 59.9–82.3%) and specificity was 100% (95% CI 92.7–89.4%-100%). In the pediatric group sensitivity of mouth culture was 78.3% (95% CI 65.8–87.9%) and specificity was 100% (95% CI 92.5–100%). Conclusion Our study demonstrated higher sensitivity of mouth culture for GAS than previously published. This finding suggests that areas of the oral cavity that were considered as unacceptable sites for culture of GAS pharyngitis may be considered as acceptable swabbing sites. Trial registration Trial registration: ClinicalTrials.gov , ID NCT03137823 . Registered 3 May 2017.